ЖИЙЕН ЖЫРАЎ – ИМПРОВИЗАТОР ШАЙЫР - Матимов, К.Г. (SCIENCE and SOCIETY, 2024)
The article studies the great representative of the Karakalpak literature of the 18th century, Djien Zhirov, was a poet (improviser) performer in the national spiritual and cultural life of our people. It is said that Zhien Zhirov took his place in the history of Karakalpak literature and was the creator of improvisation style based on traditions.
Keywords: improvisation; tradition; folk art; jirov-poet (bard); Jiyen jirov